About chemistry of tourmaline from Mnogovershinnoe ore deposit (Khabarovsk Krai, Far East) - Baksheev Ivan Andreevich; Vlasov Evgeniy Alekseevich (Федеральное государственное бюджетное образовательное учреждение высшего образования «Уральский государственный горный университет», 2019)
Relevance of the work is due to the need to study the mineralogy of gold deposits in the Russian Far East, information about which is extremely scarce. Purpose of the work: study of the chemical composition of tourmaline from Mnogovershinnoe ore deposit, Khabarovsk Krai (Far East). Methodology of research: The chemical composition of minerals and BSE images were obtained using a Jeol JSM-6480 electron microscope equipped with an Inca Energy-350 EDS (analyst is N. N. Koshlyakova, Department of Petrology, Lomonosov Moscow State University). Electron microscope shooting environment: accelerating voltage is 15 kV, measuring current for the sample is 30 ± 0.1 nA. XPP corrections were used for the adjustment procedure (INCA program, version 17a). Results. The obtained data show that tourmalines of the Mnogovershinnoe deposit differ in their chemical composition and type of substitution. All studied tourmalines by these parameters can be divided into two groups. Group 1 includes schorl, foitite, and pegmatoids feruvite, as well as schorl and foitite of the first generation, tourmaline-muscovite-quartz veinlet in sandstones. Group 2 includes schorl of the second generation, tourmalinemuscovite quartz veinlet, schorl and foitite of quartz-tourmaline metasomatites, and cement dravite of quartz breccia. Conclusions. Tourmalines of the post-ore mineral associations of the Mnogovershinnoe gold deposit are divided into two groups characterized by different chemical composition and substitutions. Tourmalines of the first group with substitutions Fe ↔ Mg and X-vacancy + Al ↔ Na + R2+ are confined to pegmatoids and were formed in reducing or weakly oxidative conditions. Later tourmalines of the second group with substitutions Fe3+ ↔ Al and Al + O2– ↔ R2++ OH– indicate a possible porphyry-style mineralization and its formation during lowering oxidative potential.
Keywords: tourmaline; chemical composition; altered rocks; Mnogovershinnoe deposit; Khabarovsk Krai; Far East; турмалин; химический состав; метасоматиты; Многовершинное рудное поле; Хабаровский край; Дальний Восток; 549.612(571.63)